Jigless knotless internal brace versus other open Achilles tendon repairs using a progressive rehabilitation protocol: a biomechanical study - Po-Yen Ko; Chieh-Hsiang Hsu; Chih-Kai Hong; Ming-Tung Hung; Wei-Ren Su; Po-Ting Wu; I-Ming Jou; Fong-Chin Su (BMC Musculoskeletal Disorders, 2021)
Abstract Background The jigless knotless internal brace surgery (JKIB), a modified minimal invasive surgery (MIS) for acute Achilles tendon injury, has advantages of preventing sural-nerve injury in MIS and superficial wound infection in open surgery, as demonstrated in previous clinical research. However, to date, biomechanical testing has not yet been validated. Materials and methods Sixty fresh porcine Achilles tendons were used to compare the JKIB with other open surgery techniques, the four-stranded Krackow suture (4sK) and the triple-bundle suture (TBS) in biomechanical testing with cyclic loading set at 1 Hz. This approach simulated a progressive rehabilitation protocol where 20-100 N was applied in the first 1000 cycles, followed by 20-190 N in the second 1000 cycles, and then 20-369 N in the third 1000 cycles. The cycles leading to repair gaps of 2 mm, 5 mm, and 10 mm were recorded. The survival cycles were defined as repair gap of 10 mm. Results With respect to survival cycles, a significant difference was found among the three groups, in which the TBS was the most robust, followed by the JKIB and the 4sK, where the mean survived cycles were 2639.3 +/− 263.55, 2073.6 +/− 319.92, and 1425.25 +/− 268.96, respectively. Significant differences were verified via a post hoc analysis with the Mann–Whitney U test after the Bonferroni correction (p < 0.017). Conclusions The TBS was the strongest suture structure in acute Achilles tendon repair. However, the JKIB could be an option in acute Achilles tendon repair with the MIS technique due to it being more robust than the 4sK, which has been typically favored for use in open repair.